Training of the Curriculum (K-13) e-Rapor Information System for the Teachers of Senior High School - Sabam Parjuangan; M Dwiyan Aditiya; Nurfiana Nurfiana (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2020)
The curriculum transformation of primary and secondary educationin Indonesia had stimulated the transformations movement of technology. Oneof these transformations was in the form of the student grade report (e-rapor) inIndonesian schools. This transformation required primary and secondary schoolteachers to be adapted to use information technology. The efforts to answer thistransformation were carried out through the technical guidance to providetraining for teachers of Sekolah Menengah Atas (SMA) and Sekolah MenengahKejuruan (SMK) Persada Bandar Lampung by filling out this e-Rapor. Thistraining was carried out through several main materials i.e., the applicationinstallation, the application troubleshooting, and the use of e-Rapor. Thistraining was implemented in 3 days. Moreover, the next training was alsoconducted to deal with some of the arising problems after the technical guidancewas conducted. This technical guidance was attended by 27 teachers. Thistechnical guidance was implemented by delivering material, conducting thesimulation, and doing discussion. The result of this technical guidance wasanalyzed quantitatively through observations and discussions. It showed that alltechnical guidance participants were able to fill out the e-Rapor systemaccording to their respective roles after the technical guidance implementationon filling out the e-Rapor.